Postcarotid Endarterectomy Hematoma Induced Arrhythmia: Report of a Rare Case - George Galyfos; Alexandros Chamzin; Fragiska Sigala; Konstantinos Filis (Case Reports in Vascular Medicine)
Postcarotid endarterectomy (CEA) hematomas are common although they are rarely threatening and necessitate reoperation. We aim to report a rare case of an expanding hematoma that caused a cardiac arrhythmia (bigeminy) which was reversed after hematoma evacuation.